Epilepsy, Temporal Lobe Sclerosis and Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Sixteen of 48 children undergoing temporal lobectomy for temporal lobe epilepsy at the Hospital for Sick Children, Toronto, Ontario, were found to have tumors (12 patients), vascular malformations (3), and arachnoid cyst (1).